Mezzanine financing as alternative source of financing for enterprises - Svědík, Jan; Tetřevová, Liběna (University of Pardubice, 2011)
The article is devoted to problem issues of mezzanine financing as an alternative source of financing for enterprises. This article aims to explain the nature and role of mezzanine financing in the enterprises and evaluates its possible use in the Czech Republic. Firstly, it defines a term of “mezzanine” in a historical context. Further possible mezzanine instruments are identified and characterized. Attention is also paid to the use of mezzanine financing from the point of corporate objectives. Finally, the situation is evaluated from the viewpoint of the use of mezzanine financing in the Czech Republic within the context of potential development.